Intelligent Recommendation module for more than one emergency vehicles node to destination node - safar, farah younus; Kareem, Emad I. Abdul (International Journal of Scientific Research and Management (IJSRM), 2018)
Traffic congestion may impede the power of emergency vehicles to arrive at the site of a traffic incident or other catastrophe in a fast and true way. Id's may not be a short one, but it is the optimal path that leads to the scene without passing in con-gested streets. Streets may be congestion for a long time and lead to not reach emergency vehicles to the destination place while other emergency vehicles can reach to the same destination place in fast which is far from the destination with uncrowded streets. This makes the emergency vehicle to reach the destination in fast. In this paper, The proposed module rep-resented in a map to show the algorithm for more than one source nodes to the destination node. In addition, a case study of a real city in Baghdad has been used to evaluate the proposed module. The results show the proposed module ability to find the optimal path with 27 to 204 seconds to give a clear recommendation for which vehicle must be moved to the destination node.